Adapting to the therapeutic recommendations of patients treated of type 2 diabetes - Natalia Alicja Świątoniowska; Beata Jankowska-Polańska (Kazimierz Wielki University, 2017)
Introduction.  Year after year, more and more people are suffering from diabetes, the number  of people with diabetes in 2012 confirms its fourfold increase over the last 35 years. It is estimated that in 2035, diabetes will be diagnosed in every third person. Currently the treatment of type 2 diabetes is based on glycemic control and avoidance  of complications. These goals can be achieved through lifestyle changes, the use  of hypoglycaemic drugs, and insulin injections. Achieving correct glycemic control is only possible if patients follow therapeutic recommendations. Data in the literature indicate that only 50% of patients follow established therapeutic regimens. Aim. The aim of the study is the presentation of previous state of knowledge on the adherence in type 2 diabetes. Brief description of state of knowledge. At present, there are few studies available assessing the level of adherence to the recommendations by patients with diabetes and adherence factors. Available publications indicate conflicting results regarding the influence of age, sex and duration  of the disease on the level of compliance. Conclusions. It is necessary to conduct further analysis of the causes of non-compliance, to select non-adherence-prone patients, and to implement methods to improve adherence to treatment recommendations in case of diabetes.